2021
DOI: 10.1080/07481187.2021.1879318
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural measurement invariance of the fear of COVID-19 scale in seven Latin American countries

Abstract: Cross-cultural measurement invariance of the fear of COVID-19 scale in seven Latin American countries Tom as Caycho-Rodr ıguez a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 79 publications
3
35
0
6
Order By: Relevance
“…The scientific literature points out that fear of COVID-19 is related to a greater extent to anxiety and to a lesser extent to depression (Ahorsu et al, 2020;Bitan et al, 2020). A recent study that evaluated fear of COVID-19 in seven Latin American countries (Argentina, Ecuador, Colombia, Mexico, El Salvador, Uruguay, and Paraguay), reported that the emotional and physiological reactions to fear differed significantly between countries, where the differences were small between Colombia, Ecuador, El Salvador, Mexico, and Paraguay; but in Argentina and Uruguay fear was much lower than the other countries (Caycho-Rodríguez et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific literature points out that fear of COVID-19 is related to a greater extent to anxiety and to a lesser extent to depression (Ahorsu et al, 2020;Bitan et al, 2020). A recent study that evaluated fear of COVID-19 in seven Latin American countries (Argentina, Ecuador, Colombia, Mexico, El Salvador, Uruguay, and Paraguay), reported that the emotional and physiological reactions to fear differed significantly between countries, where the differences were small between Colombia, Ecuador, El Salvador, Mexico, and Paraguay; but in Argentina and Uruguay fear was much lower than the other countries (Caycho-Rodríguez et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Inversely, the absence of fear can be detrimental, generating a decrease in hygiene behaviors and leading to ignoring measures aimed at mitigating the spread of the disease (Taylor, 2019). On the other hand, when fear is excessive it could become maladaptive (Mertens et al, 2020), having the potential to generate phobias, as well as higher levels of depression, anxiety, stress and addictive substance use (Asmundson and Taylor, 2020;Bitan et al, 2020;Caycho-Rodríguez et al, 2020, 2021bDoshi et al, 2020;Haktanir et al, 2020;Sakib et al, 2020). The scientific literature points out that fear of COVID-19 is related to a greater extent to anxiety and to a lesser extent to depression (Ahorsu et al, 2020;Bitan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a bifactor structure proved to be the best fit in the Ecuadorian sample (Moreta-Herrera et al, 2021 ). However, evidence from recent cross-nation measurement invariance studies showed that FCV-19S is one-dimensional in 11 countries (Lin et al, 2021 ), while another study found that the scale has a two-factor structure among seven Latin American countries (Caycho-Rodríguez et al, 2021 ). These differences in findings indicate that the factor structure of FCV-19S merits further research.…”
Section: Introductionmentioning
confidence: 99%
“…Al compararse con un estudio anterior a la situación de la pandemia 24 el número de casos relacionados con la depresión y la ansiedad ha incrementado considerablemente. A su vez, coincide con algunos estudios recientes que han encontrado prevalencias altas de ansiedad y depresión en la población general salvadoreña 5,7,8 .…”
Section: Discussionunclassified
“…En la actualidad, la población mundial atraviesa una crisis sanitaria debido a la pandemia por la COVID-19 decretada desde el 11 de marzo de 2020 por la Organización Mundial para la Salud (OMS) 1 . En estas circunstancias de incertidumbre, múltiples investigaciones evidenciaron diversas afectaciones de índole psicológica en la población salvadoreña [2][3][4][5][6][7][8] . En El Salvador, desde antes de la pandemia por la COVID-19, se había identificado la existencia de alteraciones en la salud mental en distintos sectores poblacionales [9][10][11][12] y desde el inicio de la cuarentena, emociones como el aburrimiento, el insomnio, el miedo y el enojo se presentaron en la población salvadoreña, así como otras situaciones más complejas ocasionadas por la situación de estrés, la depresión y la ansiedad que afectaron la salud mental de los salvadoreños 6 .…”
Section: Introductionunclassified